(3GdbGfhf GdJLGQj (B:s (3GdChQGb GdJLGQjI hGdEadGS (B/s - (3GdHGQhOj, Ydjs ((3GdEScfOQjI(B: s (3OGQ GdeWHhYGJ GdLGeYjI(B, s, 2000)
(3GdChQGb GdJLGQjI(B- (3GdceHjGdI(B- (3JOGhd GdceHjGdI(B- (3VeGfGJ GdhaGA HGdceHjGdI(B- (3GdSbhW hGdJbGOe(B- (3CKQ GdJYGed HGdceHjGdI aj GdOjf GdGUdj(B- (3GdEadGS(B- (3TgQ GdEadGS(B- (3GdBKGQ GdeJQJHI Ydi Mce GdEadGS(B- (3eUjQ GdJadjSIs
Keywords: (3GdChQGb GdeGdjIs; (3GdJLGQIs; (3GdbGfhfs